The centroid of a triangle is the point where the medians of the triangle meet. So we can find the centroid by determining the point of contact of two medians.

In the given triangle, the midpoint of (6, 4) and ( 3,1) is [( 6 + 3)/2 , (4 + 1)/2]. The equation of the line joining (0, 4) and ( 9/2 , 5/2) is

y – 4 = [( 4 – 5/2)/(0-9/2)]*(x – 0)

=> y – 4 = [(3/2) / (-9/2)]( x – 0)

=> -3 ( y – 4) = x

=> x + 3y – 12 = 0

The midpoint of ( 3,1) and (0, 4) is ( 3/2 , 5/2)

The line joining (6 , 4) and ( 3/2 , 5/2) is

y – 4 = [( 4 – 5/2)/(6 – 3/2)]( x – 6)

=> y – 4 = [( 3/2)/(9/2)]( x – 6)

=> 3(y – 4) = ( x – 6)

=> x - 3y + 6 = 0

We now need the point of intersection of x + 3y – 12 = 0 and x - 3y + 6 = 0.

Adding the two equations: 2x - 6 = 0 or x = 3 and substituting x = 3 in x + 3y - 12 = 0 gives y = 3.

**The centroid of the traingle is (3 , 3)**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.